Advancements in nanoparticle-based vaccine development against Japanese encephalitis virus: a systematic review - Adugna, Takele; Niu, Qingli; Guan, Guiquan; Du, Junzheng; Yang, Jifei; Tian, Zhancheng; Yin, Hong (Frontiers in Immunology, 2024)
Vaccination remains the sole effective strategy for combating Japanese encephalitis (JE). Both inactivated and live attenuated vaccines exhibit robust immunogenicity. However, the production of these conventional vaccine modalities necessitates extensive cultivation of the pathogen, incurring substantial costs and presenting significant biosafety risks. Moreover, the administration of live pathogens poses potential hazards for individuals or animals with compromised immune systems or other health vulnerabilities. Subsequently, ongoing research endeavors are focused on the development of next-generation JE vaccines utilizing nanoparticle (NP) platforms. This systematic review seeks to aggregate the research findings pertaining to NP-based vaccine development against JE. A thorough literature search was conducted across established English-language databases for research articles on JE NP vaccine development published between 2000 and 2023. A total of twenty-eight published studies were selected for detailed analysis in this review. Of these, 16 studies (57.14%) concentrated on virus-like particles (VLPs) employing various structural proteins. Other approaches, including sub-viral particles (SVPs), biopolymers, and both synthetic and inorganic NP platforms, were utilized to a lesser extent. The results of these investigations indicated that, despite variations in the usage of adjuvants, dosages, NP types, antigenic proteins, and animal models employed across different studies, the candidate NP vaccines developed were capable of eliciting enhanced humoral and cellular adaptive immune responses, providing effective protection (70–100%) for immunized mice against lethal challenges posed by virulent Japanese encephalitis virus (JEV). In conclusion, prospective next-generation JE vaccines for humans and animals may emerge from these candidate formulations following further evaluation in subsequent vaccine development phases.